Synthesis, characterization, and biological and anticancer studies of mixed ligand complexes with Schiff base and 2, 2′‐bipyridine. (10th February 2017) - Omar, M.M.; Abd El‐Halim, Hanan F.; Khalil, Eman A.M.
Abstract : New mixed ligand complexes of transition metals were synthesized from a Schiff base (L 1 ) obtained by the condensation reaction of oxamide and furfural as primary ligand and 2, 2′‐bipyridine (L 2 ) as secondary ligand. The ligands and their metal complexes were studied using various spectroscopic methods. Also thermal analyses were conducted. The mixed ligand complexes were found to have formulae [M(L 1 )(L 2 )]Cl m ⋅ n H2 O (M = Cr(III) and Fe(III): m = 3, n = 0; M = Cu(II) and Cd(II): m = 2, n = 1; M = Mn(II), Co(II), Ni(II) and Zn(II): m = 2, n = 0). The resultant data revealed that the metal complexes have octahedral structure. Also, the mixed ligand complexes are electrolytic. The biological and anticancer activities of the new compounds were tested against breast cancer (MCF‐7) and colon cancer (HCT‐116) cell lines. The results showed high activity for the synthesized compounds. Abstract : Anticancer activities of Schiff base ligand and its mixed ligand complexes for MCF‐7 cell line (breast cancer). A new Schiff base ligand and its transition metal mixed ligand complexes were prepared and characterized using various spectral and physicochemical methods. The biological and anticancer activities of the compounds were also investigated.